Assessing the Impact of Results-Based Financing on Health System Strengthening in Zimbabwe: A Case Study of Marondera and Zvishavane Districts - Manyera, Artwell; Zinyama, Tawanda; Sachikonye, Lloyd (African Journal of Inter/Multidisciplinary Studies, 2025)
The study aims to assess how the Results-Based Finance programme in Zimbabwe strengthened the health system, guided by the World Health Organisation’s six building blocks, using a case study of Marondera and Zvishavane districts. The study's findings are based on responses from focus group discussions, in-depth interviews, observations, RBF programme progress reports and closed-ended questionnaires. Therefore, a mixed research approach was adopted. The researchers administered 224 close-ended questionnaires amongst women of childbearing age and guardians. Women of childbearing age were sampled through a multi-stage sampling technique, while guardians were conveniently sampled. Qualitative data were gathered from purposively sampled key informants. It was noted that the RBF programme overwhelmingly strengthened the health delivery system between 2011 and 2018. Drastic changes were noticed in 2019 after the institutionalisation of the RBF programme in the Marondera and Zvishavane districts. This resultantly weakened the six building blocks. The COVID-19 pandemic exacerbated the situation. The study recommends that an incremental approach must be adopted when transitioning from donor support to full-time ownership of the RBF programme. The Government of Zimbabwe must commit itself to allocating 15% of the annual budget to the Ministry of Health and Child Care as envisaged by the Abuja declaration.